2019
DOI: 10.1590/0104-6632.20190362s20180308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Activity of Natural Extracts on the Oxidative Stability of Cottonseed Biodiesel

Abstract: The objective of this study was to evaluate the antioxidant activity of the natural extracts catechin, curcumin and quercetin on the oxidative stability of methylic cottonseed oil biodiesel. The oxidative stability was evaluated using the Rancimat method (EN 14112) for biodiesel with 500, 1000, 1500, 2000 and 3000 ppm of additives, and compared with the commercial antioxidant butyl hydroxyanisole at the same concentrations. Kinematic viscosity was also evaluated at the same concentration. All additives had a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It can be observed that the addition of antioxidants to biodiesel to prolong storage time can also reduce KV. Previous studies reported that KV was reduced at lower concentrations of antioxidant additives PY at (500 ppm) and slightly increased at high concentrations (1000 ppm), but lower than pure biodiesel having concluded that the addition of antioxidants to biodiesel increases storage stability and also improves KV 39,43 . Similar study showed an improvement in terms of KV (5.9 mm 2 s −1 ) and stability of biodiesel, using a concentration of 3000 ppm of PY and tert‐butyl hydroxyquinone (TBHQ) 42 …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…It can be observed that the addition of antioxidants to biodiesel to prolong storage time can also reduce KV. Previous studies reported that KV was reduced at lower concentrations of antioxidant additives PY at (500 ppm) and slightly increased at high concentrations (1000 ppm), but lower than pure biodiesel having concluded that the addition of antioxidants to biodiesel increases storage stability and also improves KV 39,43 . Similar study showed an improvement in terms of KV (5.9 mm 2 s −1 ) and stability of biodiesel, using a concentration of 3000 ppm of PY and tert‐butyl hydroxyquinone (TBHQ) 42 …”
Section: Resultsmentioning
confidence: 80%
“…Previous studies reported that KV was reduced at lower concentrations of antioxidant additives PY at (500 ppm) and slightly increased at high concentrations (1000 ppm), but lower than pure biodiesel having concluded that the addition of antioxidants to biodiesel increases storage stability and also improves KV. 39,43 Similar study showed an improvement in terms of KV (5.9 mm 2 s −1 ) and stability of biodiesel, using a concentration of 3000 ppm of PY and tert-butyl hydroxyquinone (TBHQ). 42 the BHT presented values of density within the standards of (850-900 kg m −3 ) ANP, ASTM, EN (Table 1) after 1176 h, but B100 extrapolated the limits.…”
Section: Evaluation Of Storage Stabilitymentioning
confidence: 73%
“…responsible for these properties are mainly curcuminoids (curcumin, demethoxycurcumin, bisdemethoxycurcumin and cyclocurcumin), followed by phenolic acids, and flavonoids (Chumroenphat et al, 2021). (Freitas et al, 2019).…”
Section: Phenolic Compoundsmentioning
confidence: 99%